Tribological Properties of SiC Surface Modified by Laser Radiation; AIP Conference Proceedings; Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) - Orlova E. G. Evgeniya Georgievna (Technical thermal physics and nuclear energy, 2021)
Title screen